KEPEMIMPINAN TRANSFORMASIONAL DALAM PENINGKATAN MUTU PENDIDIKAN ANAK USIA DINI - Nurmiyanti, Leni; Candra, Bach Yunof (JURNAL AL-TANZIM, 2019)
Leadership is the peak of control in an organization, with the presence of a leader who can transform all activities optimally will facilitate the effectiveness and efficiency of all activities carried out together to achieve the agreed goals. This study tries to explain the advantages of transformational leadership in early childhood education management. Transformational leadership is the right choice for a leader to optimize his leadership in increasingly complex and dynamic management practices in the world of education. The method used in data collection is the method of library study (Library Research). The data is then deductively deducted and then integrated and adjusted to the concept of early childhood education. A discussion of results will be presented descriptively. Transformational leadership can improve the process and quality of early childhood education management by maintaining good relations with its members, motivating them to continue to develop, fostering a sense of belonging to the institution, motivating to fight for common interests rather than personal interests and maintaining high moral standards.